The impact of stay-at-home orders on safety and stability for women: A topical review of intimate partner violence and intimate femicide in the United States during the initial phase of COVID-19 - Sutton, Amber (Journal of family violence, 2024)
PurposeWe intend to identify the links between COVID-19, intimate partner violence (IPV), and intimate femicide (IF) for women in the United States by answering the following questions: (1) what does the existing literature say about the intersection of COVID-19, IPV, and IF and (2) what are the contributing factors leading to rates of violence against women during COVID-19?MethodThis topical review summarizes studies published on IPV and IF during the initial stages of COVID-19 covering the period of March 1, 2020, to July 31, 2021. This review identified 22 articles addressing rates of IPV and IF during COVID-19, exacerbating risk factors for women, and recommendations for responses and intervention efforts. ResultsFindings revealed an increase in help-seeking calls during the initial phase of the pandemic and COVID-related circumstances such as extended confinement, unemployment, school closures, social isolation, and financial strains intensifying women’s experiences of violence. Data also revealed an increase in purchasing firearms, which increases the risk of women being killed by an intimate partner (Lyons et al., 2020). The nexus of COVID-19 and IPV disproportionately impact women, specifically, Latina immigrants. Implications for utilizing an intersectional framework to further examine these issues and promote social and political change are provided. ConclusionSince the rates of IPV and femicide have been reported as increasing during COVID-19, understanding the complexities and stressors associated with life in a pandemic is essential for addressing inequalities women face and the health of our communities.